Caracterização microestrutural e elétrica de La(FexNi1-x)O3 sintetizado pelo método da gelatina - Rigoti, Eduardo (2013)
The present work deals with the synthesis of materials with perovskite structure with the intention of using them as cathodes in fuel cells SOFC type. The perovskite type materials were obtained by chemical synthesis method, using gelatin as the substituent of citric acid and ethylene glycol, and polymerizing acting as chelating agent. The materials were characterized by X-ray diffraction, thermal analysis, spectroscopy Fourier transform infrared, scanning electron microscopy with EDS, surface area determination by the BET method and Term Reduction Program, TPR. The compounds were also characterized by electrical conductivity for the purpose of observing the possible application of this material as a cathode for fuel cells, solid oxide SOFC. The method using gelatin and polymerizing chelating agent for the preparation of materials with the perovskite structure allows the synthesis of crystalline materials and homogeneous. The results demonstrate that the route adopted to obtain materials were effective. The distorted perovskite structure have obtained the type orthorhombic and rhombohedral; important for fuel cell cathodes. The presentation material properties required of a candidate cathode materials for fuel cells. XRD analysis contacted by the distortion of the structures of the synthesized materials. The analyzes show that the electrical conductivity obtained materials have the potential to act as a cell to the cathode of solid oxide fuel, allowing to infer an order of values for the electrical conductivities of perovskites where LaFeO3 < LaNiO3 < LaNi0,5Fe0,5O3. It can be concluded that the activity of these perovskites is due to the presence of structural defects generated that depend on the method of synthesis and the subsequent heat treatment